MiR‐155‐5p and miR‐760 mediate radiation therapy suppressed malignancy of non‐small cell lung cancer cells. (22nd March 2019) - Zhu, Lin; Xue, Feng; Cui, Ying; Liu, Shanshan; Li, Gen; Li, Jian; Guan, Bixi; Zeng, Hai; Bian, Weixin; Yang, Chuan; Zhao, Chunbo
Abstract: MicroRNAs (miRNAs) play important roles in tumorigenesis of various cancers. Recent study suggested that miRNAs are involved in the therapeutic functions of radiation during cancer treatment. We found that radiation can decrease the migration and invasion of non‐small cell lung cancer (NSCLC) cells. Mechanistically, radiation can significantly increase the expression of miR‐155‐5p and miR‐760 in NSCLC cells. Knockdown of miR‐155‐5p and miR‐760 can attenuate radiation suppressed proliferation of NSCLC cells. Among the various targets of miR‐155‐5p, radiation can decrease the expression of HIF‐1α. Similarly, radiation can also suppress the expression of IL‐6 via a miR‐760 dependent pathway. Gain and loss of function studies confirmed that both HIF‐1α and IL‐6 were involved in the radiation suppressed proliferation of NSCLC cells. Collectively, our data showed that radiation can regulate the expression of miR‐155‐5p and miR‐760 to suppress the malignancy of NSCLC cells. © 2019 BioFactors, 45(3):393–400, 2019